PENGARUH WORK ENGAGEMENT DAN JOB SATISFACTION TERHADAP TURNOVER INTENTION (PERBANDINGAN PADA GENERASI X DAN GENERASI Y) - Rinardus Bayu Dewantoro; Sylvia Diana Purba (Prosiding Working Papers Series In Management, 2018)
The purpose of this study is to determine whether the generation (millennial and non millennial) and job satisfaction groups influence the work engagement. And whether there are differences in influence in millennial and non millennial generations in response to work engagement. In addition to know the effect of work engagement and job satisfaction on turnover intention on each generation (millennial and non millennial). The object of this research is determined by two ways, first by the purposive sampling, namely by determining the object of research in the form of technology and information-based companies. Second, sampling method in this research is convenience sampling. This study took a sample of 71 respondents consisting of 35 non millennial respondents and 36 millennial respondents. Methods of data analysis using SPSS 22 with multiple regression analysis. Based on the findings obtained from this research, job satisfaction has an effect on work engagement then there is no difference in millennial and non millennial generation in response to work engagement, then work engagement and job satisfaction have significant effect to turnover intention on non millennial generation and work engagement and job satisfaction significant effect on turnover intention on millennial generation.Keywords : Generation, Job Satisfaction, job satisfaction dan turnover intention